Prison Misconduct and the Use of Alternative Resolutions by Correctional Officers in Therapeutic Communities and Other Custody Units - Weinrath, Michael (International journal of offender therapy and comparative criminology, 2024)
This mixed methods study uses official records and interviews with inmates and staff to compare misconduct in therapeutic communities (TC’s) and the use of alternative resolutions (in lieu of formal charges by correctional officers) to other prison units. Prisoner misconduct has been studied using individual self-reports or aggregate prison rates, but unit level differences between TC’s and other prison wings are often overlooked. Restorative justice and diversion approaches are much studied in the community corrections literature but correctional officer use of alternatives to charging, such as mediation, is not well understood. The study examines differences in prisoner behavior by unit function by comparing misconduct over a 24 month period in therapeutic communities to general population, worker, protective custody, mental health, and high risk units. Study findings show lower misconduct in TC’s, including more serious misconduct such as fights. Furthermore, a significant proportion of overall charges were diverted into alternative resolution (AR)s, particularly within therapeutic communities. Interviewees reported a different approach taken in the TC toward discipline with a greater use of interaction, informal warnings, and application of AR, as opposed to formal charges. Future research is recommended using qualitative research strategies to appraise the alternative resolution decision process and prisoner-staff perceptions of discipline.